CLASSICAL EXPERIMENT IN CINE MUSIC: सिने संगीत में शास्त्रीय प्रयोग - Chopra, Pankaj (International Journal of Research -GRANTHAALAYAH, 2015)
From the beginning of the creation man has wandered in search of happiness. Its imagination has been keeping pace with this creation and this imagination has been trying to materialize the artistic tendency. To provide stability to the beauty of nature, fine arts were born and music is considered to be the highest place in the fine arts. In the words of Dr. Nisha Rawat ji, music is the moral law of the world, it fills the human mind with colorful colors in new colors and emotions. Music brings joy to the forecourt of despair and enlivens life and enthusiasm in every substance of the world. Nowadays, from morning to evening and sometimes 24 hours and continuous music echoes in our ears in many forms. In any place or any work, music continues to spread like the haze of the sky. सृष्टि के आरम्भ से मानव आनंद की खोज में भटकता रहा है। इसकी कल्पना, इस सृष्टि के साथ तालमेल स्थापित करती रही है और यह कल्पना ही, कलात्मक प्रवृत्ति को मूर्त रूप देने की कोशिश करती रही है। प्रकृति के सौन्दर्य को स्थायित्व प्रदान करते के लिए ललित कलाओं का जन्म हुआ और ललित कलाओं में सबसे ऊँचा स्थान माना गया है, संगीत का। डाॅ0 निशा रावत जी के शब्दों में संगीत विश्व का नैतिक विधान है,यह मानव मस्तिष्क में नवीन रंग और भावनाओं मंे रंगीन उडान भरता है। संगीत निराशा के प्रांगण में आनन्द का प्रपात प्रवाहित करता है तथा विश्व के प्रत्येक पदार्थ मे जीवन और उत्साह को मुखरित करता है। आजकल सुबह से शाम तक व कभी-कभी चैबीस घंटे व अनवरत संगीत की गूँज हमारे कानों में अनेेक रूपों में पडती रहती है। कोई भी स्थान हो या कोई भी कार्य हो सब जगह आकाश की धुन्ध की भाँति संगीत का प्रसार होता रहता है।